Pengaruh edukasi gizi berbasis tiktok terhadap pengetahuan gizi dan status gizi pada remaja di SMP Batik Surakarta - Nurfadilla, Raisya Putri Citranova; Muwakhidah, Muwakhidah; Rakhma, Luluk Ria (Poltekkes Kemenkes Aceh, 2026)
Background: Interactive nutrition education using social media platforms, such as TikTok, has the potential to improve adolescents’ nutritional knowledge. However, evidence regarding its effectiveness on both knowledge and nutritional status is limited to date.Objectives: This study aimed to analyze the effect of TikTok-based nutrition education on nutritional knowledge and nutritional status among adolescents at SMP Batik Surakarta in Indonesia.Methods: This study employed a quasi-experimental design with a two-group pretest–posttest control group. The sample consisted of students aged 12–15 years, divided into a treatment group (n = 48) and a control group (n = 48). The treatment group received balanced nutrition education through three TikTok-based educational videos, whereas the control group received education through a Focus Group Discussion (FGD). Nutritional status was assessed using BMI-for-age (BAZ) and analyzed using the WHO AnthroPlus software. Data normality was tested using the Shapiro–Wilk test, which indicated non-normal distribution; therefore, the Wilcoxon and Mann–Whitney tests were applied with a significance level of p < 0.05.Results: Nutritional knowledge significantly increased in the treatment group compared to that in the control group (p<0.05). The mean increase in knowledge score was higher in the TikTok group (mean=16.06) than in the FGD group (mean=3.73). However, no significant difference was found in nutritional status before and after the intervention between the groups (p>0.05).Conclusion: TikTok-based nutrition education effectively improves adolescents nutritional knowledge but does not significantly affect their nutritional status.